(2x+8)+(3x+16)+(4x-18)+(3x-7)+(2x+25)=720

Simple and best practice solution for (2x+8)+(3x+16)+(4x-18)+(3x-7)+(2x+25)=720 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+8)+(3x+16)+(4x-18)+(3x-7)+(2x+25)=720 equation:


Simplifying
(2x + 8) + (3x + 16) + (4x + -18) + (3x + -7) + (2x + 25) = 720

Reorder the terms:
(8 + 2x) + (3x + 16) + (4x + -18) + (3x + -7) + (2x + 25) = 720

Remove parenthesis around (8 + 2x)
8 + 2x + (3x + 16) + (4x + -18) + (3x + -7) + (2x + 25) = 720

Reorder the terms:
8 + 2x + (16 + 3x) + (4x + -18) + (3x + -7) + (2x + 25) = 720

Remove parenthesis around (16 + 3x)
8 + 2x + 16 + 3x + (4x + -18) + (3x + -7) + (2x + 25) = 720

Reorder the terms:
8 + 2x + 16 + 3x + (-18 + 4x) + (3x + -7) + (2x + 25) = 720

Remove parenthesis around (-18 + 4x)
8 + 2x + 16 + 3x + -18 + 4x + (3x + -7) + (2x + 25) = 720

Reorder the terms:
8 + 2x + 16 + 3x + -18 + 4x + (-7 + 3x) + (2x + 25) = 720

Remove parenthesis around (-7 + 3x)
8 + 2x + 16 + 3x + -18 + 4x + -7 + 3x + (2x + 25) = 720

Reorder the terms:
8 + 2x + 16 + 3x + -18 + 4x + -7 + 3x + (25 + 2x) = 720

Remove parenthesis around (25 + 2x)
8 + 2x + 16 + 3x + -18 + 4x + -7 + 3x + 25 + 2x = 720

Reorder the terms:
8 + 16 + -18 + -7 + 25 + 2x + 3x + 4x + 3x + 2x = 720

Combine like terms: 8 + 16 = 24
24 + -18 + -7 + 25 + 2x + 3x + 4x + 3x + 2x = 720

Combine like terms: 24 + -18 = 6
6 + -7 + 25 + 2x + 3x + 4x + 3x + 2x = 720

Combine like terms: 6 + -7 = -1
-1 + 25 + 2x + 3x + 4x + 3x + 2x = 720

Combine like terms: -1 + 25 = 24
24 + 2x + 3x + 4x + 3x + 2x = 720

Combine like terms: 2x + 3x = 5x
24 + 5x + 4x + 3x + 2x = 720

Combine like terms: 5x + 4x = 9x
24 + 9x + 3x + 2x = 720

Combine like terms: 9x + 3x = 12x
24 + 12x + 2x = 720

Combine like terms: 12x + 2x = 14x
24 + 14x = 720

Solving
24 + 14x = 720

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 14x = 720 + -24

Combine like terms: 24 + -24 = 0
0 + 14x = 720 + -24
14x = 720 + -24

Combine like terms: 720 + -24 = 696
14x = 696

Divide each side by '14'.
x = 49.71428571

Simplifying
x = 49.71428571

See similar equations:

| 8+4v=-4 | | 4a+6-3a-2= | | S/-3=2 | | h=2*3.14*r^2+2*3.14*r*16.2 | | 25n-40=-62 | | 3/4(8y-12)= | | .75t=50 | | F(x)=12x-6 | | 8(-5+4)= | | .75t=.50 | | (2y+9)(2y+9)=81 | | (4-2j)/(2-1j) | | 5.26s-2.01=-8.94 | | -2g+7= | | -9s+18-18=18s-4-2 | | 7v+224=-84v | | 3v+9+v=2v-2+3 | | -38-37= | | 10+5x-x=10+4x+4 | | 45=26+b | | X+2+x-10=90 | | 2v+1=-3v+8v+10 | | 6u-12+2=6u-10 | | 14m-2m-2m-8m=12 | | 45=26 | | h=2*3.14*30.25+2*3.14*5.5*18.7 | | 3y+6-y=2y-2+10 | | 729/1.000 | | 6x+12=3x-9 | | 14g-13g=17 | | -2x-4+7=3x+18 | | 4x-2(x-2)=-5+4x-3 |

Equations solver categories